2023
DOI: 10.3390/su15097584
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Plant Functional Traits and Soil Carbon Sequestration under Ambient and Elevated CO2 Levels

Abstract: Unique plant functional traits (morpho-physio-anatomical) may respond to novel environmental conditions to counterbalance elevated carbon dioxide (eCO2) concentrations. Utilizing CO2, plants produce photoassimilates (carbohydrates). A mechanistic understanding of partitioning and translocation of carbon/photoassimilates into different plant parts and soils under ambient and eCO2 is required. In this study, we examine and present the intrinsic relationship between plant functional traits and eCO2 and seek answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 198 publications
0
1
0
Order By: Relevance
“…Indeed, high concentrations of As and Cu have been found in Cupressus macrocarpa leaves in the studied area (Gorena et al, 2020). Besides, trees can improve soil C sequestration, improving air quality and soils (Bhattacharyya et al, 2023). The latter is essential to the study area because loss of soil organic matter has been identified as the primary driver of desertification in the studied area (Ginocchio, 2000;Pardo et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, high concentrations of As and Cu have been found in Cupressus macrocarpa leaves in the studied area (Gorena et al, 2020). Besides, trees can improve soil C sequestration, improving air quality and soils (Bhattacharyya et al, 2023). The latter is essential to the study area because loss of soil organic matter has been identified as the primary driver of desertification in the studied area (Ginocchio, 2000;Pardo et al, 2018).…”
Section: Discussionmentioning
confidence: 94%